Association of Lipid Profile With Cardiovascular Diseases and All‐Cause Death: A 2‐Decade Follow‐Up of the Tehran Lipid and Glucose Study - Azra Ramezankhani; Fereidoun Azizi; Farzad Hadaegh (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background We investigated the associations between total cholesterol, low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol (HDL‐C), non–HDL‐C, and triglycerides with all‐cause and cardiovascular disease death among participants in the TLGS (Tehran Lipid and Glucose Study) cohort. Methods We included 8241 participants aged ≥30 years, who were followed until 2018. Lipid profiles were assessed as both continuous and categorical variables (quintiles) using the restricted cubic spline and Cox proportional hazards model. Results During a median follow‐up of 18.1 years, 1002 and 369 individuals died from all causes and cardiovascular disease, respectively. A U‐shaped association was found between non–HDL‐C and the risk of all‐cause death. In the categorical analyses for all‐cause death, individuals in quintile 1 of non–HDL‐C had a hazard ratio (HR) of 1.35 (95% CI, 1.09–1.68), compared with quintile 2 (reference). Additionally, those in quintiles 1 and 3 of total cholesterol had HRs of 1.34 (95% CI, 1.08–1.67) and 1.25 (95% CI, 1.02–1.55), respectively, relative to quintile 2 (reference). Regarding cardiovascular disease death, linear associations were observed for total cholesterol, low‐density lipoprotein cholesterol, and non–HDL‐C. In categorical analysis, quintiles 3 and 5 of total cholesterol had HRs of 1.87 (95% CI, 1.30–2.70) and 1.78 (95% CI, 1.25–2.53), respectively, compared with quintile 2 (reference). Furthermore, compared with quintile 1 of low‐density lipoprotein cholesterol (reference), individuals in quintiles 3 and 5 had HRs of 1.62 (95% CI, 1.08–2.42) and 1.81 (95% CI, 1.24–2.66), respectively. For non–HDL‐C, the HR for quintile 5 was 1.43 (95% CI, 1.00–2.06) compared with quintile 1 (reference). Conclusions In the general population, low and high levels of non–HDL‐C were associated with an increased risk of all‐cause death.